Ecosystem services to support environmental and socially sustainable decision-making - Rusch, Veronica Elena; Rusch, Graciela Mónica; Goijman, Andrea Paula; Varela, Santiago Agustin; Claps, Leonardo (Ecología Austral, 2017)
The theory of ecosystem services (ES) needs to be operationalized to contribute to practices leading to sustainable use of ecosystems, which includes solving trade-offs between private and public benefits and incorporating monetary and non-monetary values to help inform decisions. We developed a framework to analyse the impacts of farmers’ management alternatives on Nothofagus antarctica (G. Forst.) Oerst. forest in northern Patagonia, and analysed synergies and trade-offs between private and public benefits based on three conceptual and methodological approaches: a) a state-and-transition model of ecosystem dynamics, and b) indicators of values of ecosystem service benefits based on the cascade model, implemented as c) a decision support tool based on a Bayesian network. We optimized a utility function for short (0-10 yr) and long (70-140 yr) term management decisions (levels of grazing, logging and tree planting) based on monetary and non-monetary indicators of benefits that fulfilled “farmer’s satisfaction” objectives. We then assessed the consequences of these decisions on the fulfilment of public benefits as defined by the National Forest Law when projected into short (0-10 yr), intermediate (10-40 yr) and long (70-140 yr) time horizons. We found that when short-term decisions are projected into a long-time horizon, they lead to high losses of benefits, mainly linked to “regulating and maintenance” ES. On the other hand, long-term decisions improved the level of benefits in degraded systems but resulted in the degradation of well-preserved forests. The decisions that optimize farmer’s satisfaction did not change with different weights of “farm income” in the utility function, indicating the absence of trade-offs between monetary and non-monetary benefits considered in the utility function. The tool developed helps to show long-term impacts of management, and discloses cause-effect relationships between levels of use and multiple benefits. It can therefore support measures aiming to raise awareness about degradation trends, and improve the functional understanding of the system wich can help to identify solutions for socio-economic and environmental sustainability. La teoría de los servicios ecosistémicos debe hacerse operativa para poder contribuir a la formulación de prácticas que conduzcan al manejo sustentable de los ecosistemas. Esto incluye contribuir a resolver los conflictos entre beneficios privados y públicos, e incorporar valores monetarios y no-monetarios para poder informar la toma de decisiones. Desarrollamos un modelo para analizar el impacto de las decisiones de manejo de los productores en el bosque de Nothofagus antarctica (G. Forst.) Oerst. del norte de la Patagonia y analizamos las sinergias y los conflictos entre los beneficios públicos y privados en base a tres marcos conceptuales y metodológicos: a) un modelo de estados y transiciones de la dinámica del ecosistema, y b) indicadores de los servicios ecosistémicos generados sobre la base del modelo de cascada, implementado como c) un sistema de apoyo a la toma de decisiones basado en redes Bayesianas. Optimizamos la función de utilidad sobre decisiones de manejo (niveles de pastoreo, extracción de madera y plantación de árboles), para lo cual nos apoyamos en indicadores de beneficios monetarios y no monetarios que satisfacen los objetivos del productor a corto (0-10 años) y largo (70-140 años) plazo. Luego, determinamos las consecuencias de las soluciones cercanas al óptimo en términos de satisfacción de beneficios públicos de acuerdo con su formulación en la Ley Nacional de Bosques. Encontramos que cuando las decisiones que optimizan los beneficios a corto plazo se proyectan en el tiempo (70-140 años), resultan en pérdidas altas de beneficios, especialmente, los ligados a servicios ecosistémicos de “regulación y mantenimiento”. Por otro lado, las decisiones que optimizan los beneficios a largo plazo mejoran el nivel de beneficios en los estados degradados, pero al mismo tiempo, desmejoran la condición del bosque en buen estado de conservación. Las decisiones que optimizan la satisfacción del productor no cambian con los distintos pesos de la variable ‘ingreso predial’, indicando que no existe conflicto entre los beneficios monetarios y no-monetarios en la función de utilidad. La herramienta desarrollada ayuda a visualizar los impactos a largo plazo y revela relaciones de causa-efecto entre los niveles de uso y los múltiples beneficios generados por el sistema. Por ello, puede asistir a formular medidas que generen conciencia sobre las tendencias de degradación y contribuir, de este modo, a identificar soluciones para lograr la sustentabilidad socioeconómica y ambiental. Estación Experimental Agropecuaria Bariloche. Área Sistemas Forestales. Grupo de Ecología Forestal Fil: Rusch, Verónica Elena. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche. Área Sistemas Forestales. Grupo de Ecología Forestal; Argentina Fil: Rusch, Graciela Mónica. Norwegian Institute for Nature Research; Noruega Fil: Goijman, Andrea Paula. Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto de Recursos Biológicos; Argentina Fil: Varela, Santiago Agustín. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Barilohe. Área Sistemas Forestales. Grupo de Ecología Forestal; Argentina Fil: Claps, Leonardo. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche; Argentina